Scintigraphy with99mTc-Tripolyphosphate in the Early Diagnosis of Osteomyelitis - Hemborg, A.; Kempi, V.; van der Linden, W. (Nuklearmedizin - NuclearMedicine, 1976)
In 14 consecutive patients with suspected osteomyelitis studies were performed with 99mTc-tripolyphos-phate. In all patients the diagnosis was ultimately verified by biopsy. In seven of the 14 patients the radiograms showed osseous lesions at the same time as the scintigraphic studies. In the other seven patients, such lesions became visible on the X ray film one to 20 weeks after their demonstration by the radioisotope method. 99mTc-tripolyphosphate appears to be a very sensitive indicator of oesteomyelitis.